Optimization of the performance of the steam turbine SCSF-31.2" with 6 stages of axial exhaust in "X" geothermal power plant (PLTP "X") - Hernawan Novianto; Zakiy Kamikho Harfy; Shultoni Mahardika; Sujono Sujono; Ayende Ayende (Jurnal POLIMESIN, 2023)
The SCSF-31.2" 6-stage axial exhaust turbine in PLTP "X" is the main equipment for the power plant unit that functions to convert heat energy from steam into kinetic energy (rotation). Kinetic energy is transmitted by the shaft to the generator and then converted into electrical energy. The SCCF-31.2" 6-stage axial exhaust turbine currently operates at 7.95 bar (a) inlet pressure, 169.7 oC inlet temperature, and 112.504 kg/s steam mass rate. After evaluating the turbine performance with current actual operating data, the efficiency value is 78.8%, and it produces a gross generator power of 54.867 MW. The current efficiency value has decreased by 9.2% when compared to the initial condition. The decrease in efficiency is expected to occur due to an increase in temperature and pressure in the condenser. The temperature and pressure inside the condenser were initially at 40 °C and 0.074 bar (a) and are currently at 45.2 °C and 0.098 bar (a). Therefore, optimization is done by cleaning the channel sprayer in the condenser with the hope of increasing the water cooling flow rate and creating a wider contact area. As a result, the condenser temperature and pressure decreased so that the turbine efficiency value increased to 81.2% and the gross generator power increased to 57,224 MW